Disaster (continued): Sewol Ferry investigations, state violence, and political history in South Korea. (2nd January 2022) - Jeon, Chihyung; Knowles, Scott Gabriel; Park, Sang-Eun
ABSTRACT: The Special Investigation Commission on the 4/16 Sewol Ferry Disaster offers a case in which the process of disaster investigation becomes a part, even a continuation, of the disaster for which it is created to bring closure. Placing the investigation in a longer temporality reveals obscured historical factors that shaped the investigation and its aftermath in surprising and crucial ways. Throughout the highly politicized process of deciding to investigate, what and whom to investigate, and how, disaster investigations can exacerbate the complexity of the disaster and the suffering of the victims and their families. What seems at first a technical and straightforward problem often turns out to be historically rooted and deeply contentious. In the case of the Sewol Ferry Disaster investigations, the process of creating an independent commission in a polarized political milieu unexpectedly formed a venue for evoking, drawing on, and re-experiencing state violence across generations. The Sewol Commission was modeled after earlier truth and reconciliation commissions in Korea, whose focus on individual 'cases' of political violence shaped how the Sewol investigation was conceptualized. As it turned out, the closure of the Sewol Commission closed nothing but the commission itself; the tragedy of the Sewol lingered.